2004
DOI: 10.1023/b:drug.0000006171.54078.3d
|View full text |Cite
|
Sign up to set email alerts
|

The Antiangiogenic Agent Neovastat (Æ-941) Stimulates Tissue Plasminogen Activator Activity

Abstract: The plasminogen activator/plasmin system represents a key component of the proteolytic machinery underlying angiogenesis. In this work, we investigated the effect of Neovastat (AE-941), a naturally occurring multifunctional antiangiogenic agent that is currently in Phase III clinical trials, on tissue and urokinase plasminogen activator activities. We found that in vitro, Neovastat at 100 microg/ml markedly stimulates t-PA-mediated plasmin generation, while it slightly inhibits the generation of plasmin mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Paradoxically, shark cartilage extract (including AE-941) also has fibrinolytic activity. 145,146 Nevertheless, fibrinolysis and anticoagulation may also reduce tumor cell metastasis. 147,148 Shark cartilage extracts are pleiotropic, having multiple phenotypic activities.…”
Section: Shark and Bovine Cartilagementioning
confidence: 99%
“…Paradoxically, shark cartilage extract (including AE-941) also has fibrinolytic activity. 145,146 Nevertheless, fibrinolysis and anticoagulation may also reduce tumor cell metastasis. 147,148 Shark cartilage extracts are pleiotropic, having multiple phenotypic activities.…”
Section: Shark and Bovine Cartilagementioning
confidence: 99%
“…These findings suggest that an increase in either PLAT activity or expression levels is beneficial, possibly due to the overstimulation of plasmin generation by PLAT that induces the degradation of the pro-angiogenic fibrin matrix, resulting in the inhibition of angiogenesis (71,72). Moreover, Gingras et al (72,73) reported that Neovastat, an inhibitor of angiogenesis derived from marine cartilage, specifically stimulates PLAT-dependent plasmin generation through an increase in the affinity of the enzyme towards plasminogen.…”
Section: Discussionmentioning
confidence: 98%
“…Neovastat inhibits CAM vascularization and Matrigel-induced angiogenesis [88]; it competitively suppresses the VEGF-dependent phosphorylation of VEGFR, the proliferation of endothelial cells, and VEGF-induced vascular permeability in mice [89]. Neovastat could also inhibit MMP-2 [90] but stimulate tissue plasminogen activator (tPA) [91] and activate caspase-mediated apoptotic pathways in endothelial cells [92]. In addition, neovastat has significant antitumor and antimetastatic activity [93].…”
Section: Marine-derived Protein Kinase Modulators With Antiangiogementioning
confidence: 99%